2022
DOI: 10.3390/ani12020141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Enrichment on Dog Behaviour: Pilot Study

Abstract: Environmental enrichment (EE) can be used to enhance the environment of various animals. The aim of this pilot study was to determine the effects of seven EE activities (Bonding, Bubble machine, Conspecific play, Interactive toy, Playhouse, Stuffed food toy and Tug play) on dog behaviour, pre- and post-EE for dogs housed in an office environment during training as part of an assistance dog training programme. EE activities resulted in a significant increase in the frequency of relaxation behaviours (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Previous studies have also studied the benefit of environmental enrichment for stress reduction. Hunt et al demonstrated that environmental enrichment increases relaxation behavior and decreases alert and stress behaviors in dogs [ 46 ]. Albanese et al reported that environmental enrichment increases their positive behavior and reduces the fecal cortisol metabolite in the study of non-human primates, which are another captive animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also studied the benefit of environmental enrichment for stress reduction. Hunt et al demonstrated that environmental enrichment increases relaxation behavior and decreases alert and stress behaviors in dogs [ 46 ]. Albanese et al reported that environmental enrichment increases their positive behavior and reduces the fecal cortisol metabolite in the study of non-human primates, which are another captive animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing directions of causation is a limitation, and further studies using experimental designs would be of use. Given that studies of kennelled dogs have found non‐food environmental enrichment to reduce stress more than CEF, 55 future studies should investigate the impacts of different types of enrichment on pet dogs within home environments.…”
Section: Discussionmentioning
confidence: 99%
“… Term Definition Whining Dog produces sounds such as whines, whimpers, yelps, etc. originating from the throat and mouth 38 Not Whining Sound production ceases 38 Panting Increased shallow respiration through an open mouth, may have tongue out 47 Mouth not visible Can not see mouth area. Panting/Not Panting cannot be determined ( defined for this study ) Not Panting Mouth is closed—normal breathing resumes 38 Yawn An involuntary intake of breath through a wide-open mouth 38 Shake Dog's whole body and/or head starts moving rapidly from side to side while the dog stands 48 Bark Head and lips forward, mouth opening and shutting repeatedly to omit a large, sharp, short sound emitted from the throat 38 Howl Raised muzzle perpendicular to ground and emits a long, drawn-out sound through semi-closed jaws.…”
Section: Methodsmentioning
confidence: 99%